THERAPEUTIC PLASMAPHERESIS IN COMPLEX PROPHILACSIS OF FETUS HEMOLYTIC DESEASE IN PREGNANT WITH RHESUS-ISOIMMUNIZATION - Chermnykh, S.V.; Galchenko, Yu.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
In the article the problems on efferent methods using in prophilacsis and complex treatment of pregnant women with isoimmunization due to rhesus-factor are discussed. The experience of the department for gravitational blood surgery of Donetsk Regional Center for Maternity and Child Care on the prevention of newborns hemolytic disease in women with the above mentioned pathology is highlighted.